Trinity : the God we don't know - Byassee, Jason (Nashville, Tennessee : Abingdon Press, 2015)
Who is this God we worship?
The God we don't talk about -- The son we don't know: how can we say Jesus is divine? -- The spirit we don't know: generous gift-give -- The triune God we don't know: appropriations and mutual indwelling: which person is working?
Includes bibliographical references.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Trinity; God (Christianity); God (Christianity).; Religion; Trinity; God (Christianity); Trinity; RELIGION / Christian Theology / General; Electronic books; Electronic books